Clinical Outcome of Orthopaedic Patients with Negative Lower Limb Venography at Discharge - Agnelli, Giancarlo; Ranucci, Valeria; Veschi, Franca; Rinonapoli, Emanuele; Lupattelli, Luciano; Nenci, Giuseppe G (Thrombosis and Haemostasis, 1995)
Pharmacological prophylaxis for postoperative venous thromboembolism is generally restricted to the hospital stay. A high incidence of deep vein thrombosis (DVT) and pulmonary embolism presenting after hospital discharge has been reported and thus it has been claimed that pharmacological prophylaxis should be continued after discharge. The aim of this study was to perform a prospective survey to assess the prevalence of clinically overt thromboembolic events in hip surgery patients discharged with a negative venography without further pharmacological prophylaxis. We followed-up 213 patients with negative venography at discharge (105 elective hip replacement and 108 hip fracture patients). 186 patients (87.3%) were re-examined as outpatients one to two months after discharge. Five patients reported symptoms of DVT but the diagnosis was not confirmed by objective testing. The remaining 27 patients (12.7%) were followed up through their family doctor or by telephone call; in these patients the follow-up period ranged from 60 days to 2 years. Twenty-two patients (10.3%) were still alive and reported no signs or symptoms of venous thromboembolism. Three patients (1.4%) died for reasons not correlated with venous thromboembolism. Two patients could not be traced due to geographical inaccessibility; they were still alive after 1 year according to the records of their health care district. The results of our study suggest that in hip surgery patients with negative venography the prevalence of clinically overt thromboembolic events after hospital discharge ranges from 0 to 2.2% (95% C. I.). It is conceivable that the majority of late presenting postoperative DVT actually develop during the hospital stay and become symptomatic after hospital discharge.